Optimization of light source wavelength for ammonia detection in water - Nurfatihah Che Abd Rashid; Noran Azizan Cholan; Kim Gaik Tay; Afiqah Yaacob; Nazrah Ilyana Sulaiman; Khairulanwar Mokhiri; Nor Hafizah Ngajikin (Universitas Ahmad Dahlan, 2022)
Optimization of light source wavelength for ammonia detection in surface water is presented in this work. For the ammonia detection, the surface water sample is mixed with sodium chloride and nessler reagent, whereas the sensor head consists of unclad plastic optical fiber. The unclad region has a length of 1 cm and the cladding is removed by immersing it in acetone solution. Experimental results indicate that the output light intensity of the sensor has linear relationship with the ammonia concentration. At the wavelength of 510 nm, the output light increases linearly as the ammonia concentration varies from 0.07 mg/L to 8.97 mg/L. At the same wavelength, the proposed sensor achieves the sensitivity of 0.0139 (mg/L)-1, accuracy of 99.59% and resolution of 0.72 µg/L. The analysis of light source wavelength reveals that a wavelength range from 450 nm to 580 nm produces the optimized performances. Within this wavelength range, the proposed sensor achieves sensitivity of higher than 0.01 (mg/L)-1, accuracy of higher than 99% and resolution of less than 1 µg/L.